Familial left ventricular noncompaction: phenotypes and clinical course. Results of the multicenter registry - Olga V. Kulikova; Roman P. Myasnikov; Elena A. Mershina; Polina S. Pilus; Sergei N. Koretskiy; Aleksei N. Meshkov; Anna V. Kiseleva; Mariia S. Kharlap; Valentin E. Sinitsyn; Nataliia A. Sdvigova; Leila A. Gandaeva; Vladimir I. Barskiy; et al. (Терапевтический архив, 2021)
Aim. To analyze and demonstrate various phenotypes in patients with familial left ventricular noncompaction (LVNC).